The Effects of Classification of Records on Effective Retrieval of Information: A Case of Kabale District Headquarters Registry. - Vivian, Kyarisiima (Kabale University, 2019)
A Research Report Submitted to the Facultyof Arts and Social Sciences in Partial fulfilment of the Requirement for the award of Diploma of Records Management of Kabale University.